Local DNA shape is a general principle of transcription factor binding specificity in Arabidopsis thaliana - Janik Sielemann (Nature Portfolio, 2021)
Methods to predict transcription factor binding sites typically focus on sequence motifs without considering DNA shape. Here the authors use a random forest machine learning approach that incorporates DNA shape and improves binding site prediction for Arabidopsis thaliana transcription factors.